Comparative genomic analysis of iprodione‐degrading Paenarthrobacter strains reveals the iprodione catabolic molecular mechanism in Paenarthrobacter sp. strain YJN‐5. (17th November 2020) - Zhang, Mingliang; Ren, Yijun; Jiang, Wankui; Wu, Chenglong; Zhou, Yidong; Wang, Hui; Ke, Zhijian; Gao, Qinqin; Liu, Xiaoan; Qiu, Jiguo; Hong, Qing
Summary: Degradation of the fungicide iprodione by the Paenarthrobacter sp. strain YJN‐5 is initiated via hydrolysis of its N1 amide bond to form N ‐(3, 5‐dichlorophenyl)‐2, 4‐dioxoimidazolidine. In this study, another iprodione‐degrading strain, Paenarthrobacter sp. YJN‐D, which harbours the same metabolic pathway as strain YJN‐5 was isolated and characterized. The genes that encode the conserved iprodione catabolic pathway were identified based on comparative analysis of the genomes of the two iprodione‐degrading Paenarthrobacter sp. and subsequent experimental validation. These genes include an amidase gene, ipaH (previously reported in AEM e01150‐18); a deacetylase gene, ddaH, which is responsible for hydantoin ring cleavage of N ‐(3, 5‐dichlorophenyl)‐2, 4‐dioxoimidazolidine, and a hydrolase gene, duaH, which is responsible for cleavage of the urea side chain of (3, 5‐dichlorophenylurea)acetic acid, thus yielding 3, 5‐dichloroaniline as the end product. These iprodione‐catabolic genes are distributed on three plasmids in strain YJN‐5 and are highly conserved between the two iprodione‐degrading Paenarthrobacter strains. However, only the ipaH gene is flanked by a mobile genetic element. Two iprodione degradation cassettes bearing ipaH ‐ ddaH ‐ duaH were constructed and expressed in strains Pseudomonas putida KT2440 and Bacillus subtilis SCK6 respectively. Our findings enhance the current understanding of the microbial degradation mechanism of iprodione.